طرق الطعن وأحكام التقادم في قانون رعاية الأحداث العراقي رقم76لسنة1983 - داوود صباح سامي; حسين اسماء ابراهيم (Journal of Legal Sciences, 2019)
The criminal case of Juvenile has privacy at all stages, hence, the amended juvenile care Act no.76 of 1983 granted juvenile the right to appeal the verdicts issued by the juvenile courts. This is normal that those verdicts be included objectivity or procedural mistakes and in order to correct these mistakes, the law has granted the juvenile this right. Also, the mentioned act became a general principle unlike the amended law of criminal trails No-23 of 1971, which has been taken as an exception to increase the juvenile protection. The international conventions that compare with our study stated explicitly on the juvenile right to appeal verdicts but it did not stated explicitly on the provision of retirement judgment. However it is understood from its texts that they took this principle, especially the cases relating to juvenile.